Teachings, Epistemology, and Thoughts of Muhammad Bin Abdul Wahhab at-Tamimi in Islamic Law - Eko Kholistio Putro; Zaenul Mahmudi; Ali Hamdan (Postgraduate Program Magister Pendidikan Agama Islam, 2021)
Muhammad bin Abdul Wahhab created a da'wah movement to purify Islamic doctrines. With this movement, he invited all Muslims to return to the Qur'an and Sunnah by the understanding of the Sahabah. This research is qualitative, using an analytical descriptive method and a normative juridical approach. This study aims to find out who Muhammad bin Abdul Wahhab was, how his doctrines, epistemology, and thoughts were in Islamic law, and how the term